2014
DOI: 10.5545/sv-jme.2013.1295
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Fault Detection of a Wind Turbine Gearbox Using Empirical Mode Decomposition

Abstract: The conventional method of detecting a gear fault is to demodulate the vibration signal collected from the gearbox based on the Hilbert transform; however, this requires human intervention and lacks sophistication. Empirical mode decomposition (EMD) is a significant timefrequency tool for adaptively decomposing vibration signals into a collection of intrinsic mode functions (IMFs); a fault feature can be extracted from one of IMFs to reveal the fault location and fault level of a gear or bearing in the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…C.Hatch [7] stressed the importance of Acceleration enveloping technique in wind turbine condition monitoring. Wei Teng et al [8] found out that Empirical Mode Decomposition is a more powerful technique than conventional demodulation techniques using Hilbert transform for identification of gear pitting failures in a wind turbine gearbox. James C. Robinson [9] found that analysis of stress waves proved to be an effective diagnostic tool for fault detection and severity assessment in gearboxes.…”
Section: Literature Survey On Various Condition Monitoring Techniquesmentioning
confidence: 99%
“…C.Hatch [7] stressed the importance of Acceleration enveloping technique in wind turbine condition monitoring. Wei Teng et al [8] found out that Empirical Mode Decomposition is a more powerful technique than conventional demodulation techniques using Hilbert transform for identification of gear pitting failures in a wind turbine gearbox. James C. Robinson [9] found that analysis of stress waves proved to be an effective diagnostic tool for fault detection and severity assessment in gearboxes.…”
Section: Literature Survey On Various Condition Monitoring Techniquesmentioning
confidence: 99%
“…Empirical mode decomposition (EMD) is a valuable time–frequency tool, especially for the non‐stationary vibration signals of wind turbines. An application of EMD on a wind turbine gearbox gear pitting fault is presented in [35]. EMD combined with energy separation can provide a framework for detecting planetary gearbox faults, as presented in [36].…”
Section: Vibration CM and Fault Detection In Wind Turbinesmentioning
confidence: 99%
“…3 has few fault feature. Teng et al [24] give the reason that the sensor of no. 1 is installed on the ribbed slab of the casing where it is not overly sensitive to the excitation of the high-speed stage.…”
Section: Two Wind Turbine Gear Fault Diagnosis Applicationmentioning
confidence: 99%